Analysis of Mother Knowledge and the Role of Parents in Toilet Training Against Enuresis Incidence in Preschool Children at TK AR-ROHIM Kalipepe - Yonni Siwi, Retno Palupi; Miftakhur Rohmah; Riza Tsalatsatul Mufida (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2021)
High incidence of enuresis in preschool children is due to several factors, namely education, employment, maternal information sources about toilet training and wrong toilet training practices, which have an impact on the high incidence of enuresis. The purpose of this study was to analyze the knowledge of mothers and the role of parents in toilet training on the incidence of enuresis in preschool children. This research is an analytical observational correlation withresearch design cross sectional. The population is all mothers who have preschool age children in TK AR-ROHIM Kalipepe as many as 40 respondents with a total sample of 36 respondents. The sampling technique uses simple random sampling. With the independent variable, namely knowledge and role, while the dependent variable is the incidence of enuresis. The research instrument used a questionnaire. The results of data analysis to see the relationship between the independent variable and the dependent variable used thestatistical test Chi-square with a significant technique α = 0.05. The results showed that of the 36 respondents, most of the mothers' knowledge about toilet training was good, namely 19 people (52.8%), the role of parents towards toilet training was good, namely 27 people (75%) and 20 children (55.6%) experienced enuresis. . According to the results of thetest, it chi-square (x2)shows that the p value > α (0.05) and there are cells that have an expected frequency of less than 5. It can be said that thetest conditions chi-squareare not met. So that the relationship test is guided by the results of the Fisher's Exact Test. Results Exact Sig (2-sided) = 0.644. Because the test value> α (0.05), it is concluded that Ho is accepted and H1 is rejected, meaning that there is no significant effect between knowledge and parental roles on the incidence of enuresis in preschool children in TK AR-ROHIM Kalipepe. So that promotive and preventive efforts from health workers need to be done to be able to reduce the high incidence of enuresis in preschool children.